Percurso histórico-teológico do ecumenismo à luz do Magistério do Papa Francisco - Silva, Diego Nascimento (2022)
This dissertation sought to trace the historical-theological course of the ecumeniscism down the road of the Christian unity, looking at what is there in common in Catholicism, by the special optics of Pope Francis' teaching position, and the historical churches. In this way, this research looked for the historical events that have marked the Christianism, left of the prayer made by Jesus in the gospel of John, indicates very clearly that a division between christians is a real scandal to the world, also bringing the major conflicts inside the Christianism, all this led the emergence of new christian churches separated of the Catholicism. The schisms that worked in the beginning of this research, far from being the only ones, were addressed here in the perspective that with them, new communities have been born. And the shock between churches, that was one someday, was tragic and extreme, because both sides in the dispute used accusations and violence even drawing to homicides in the two sides. Even though big steps were made to take this to a dialogue, the last century (XIX), have been marked by the extremism among the religious thoughts, that despises those steps to get this ecumenic dialogue, putting into discredit the Gospel itself. Given this picture, the urgent need to recover the meaning and the purpose of the Ecumenicism, because from it not only the Gospel would be announced with more credibility, as well the Eumenism field will show itself as the way, started and followed through, to open more doors to the understanding that the other ones faith, professed in a different way, is not an enemy to be fought, but one more brother to be welcomed. The Vatican II was a watershed to the church itself; in the present days, even through oppositions, the catholicism lives in a time of renewals, caused by the election of Francis that seems to live an ecclesiology marked by the Council. On the basis of Francis gestures and lessons, the flame of the ecumenical works reascent, because there is a lot to be made, the ecumenicism isn’t an addendum to the Church, but a fundamental part of your way of thinking and acting in the world, specially in front to the increasing number of radical groups and fundamentalists